Legal Analysis of Aircraft as Credit Collateral in Guarantee Law in Indonesia - Nugraha, Naufal Akmal Bintang (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The current Aviation Law does not regulate the binding of mortgage guarantees on aircraft, causing legal uncertainty regarding aircraft as collateral. There are differing opinions on which guarantee institution is appropriate for imposing guarantees on aircraft according to Indonesian law. To date, mortgage collateral is considered the most relevant for binding aircraft because aircraft have special characteristics. Aircraft are registered and have a country mark, so they can legally be used as collateral for debt repayment. Therefore, the binding of aircraft and helicopters is done with a mortgage. The research method used is a normative juridical descriptive method with the object of research being guarantees on aircraft. The results of this study indicate that there are no government regulations concerning the imposition of security rights on aircraft, making the process unclear. Notaries are authorized to make aircraft mortgage deeds, providing certainty and legal protection. Notaries can also make SKMH, which has perfect legal proof. The existence of SKMH in the guarantee of aircraft security rights is the choice of the related parties. In essence, the imposition of mortgages must be done with an authentic deed made before a competent official, in this case, a notary, according to Article 1338 of the Civil Code (BW) and Article 1171 of the Civil Code (BW).